2008
DOI: 10.1111/j.1463-6409.2008.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the genus Rotylenchus (Nematoda, Tylenchida) and description of a new species

Abstract: A description of a new species of plant parasitic nematodes of the genus Rotylenchus from the family Hoplolaimidae is given and a recognition of Rotylenchus jaeni comb. n., previously known as subspecies R. magnus jaeni, as separate species is proposed. Rotylenchus montanus sp. n. is characterized by a hemispherical lip region with six rarely seven annuli, stylet 33–37 µm, female tail rounded, regularly annulated tip with 12–18 annuli and phasmid located 2–9 annuli anterior to anus. Rotylenchus montanus sp. n.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
(23 reference statements)
6
41
1
Order By: Relevance
“…As in recent contributions (Cantalapiedra-Navarrete et al, 2012, 2013, the phylogenetic relationship showed that R. conicaudaus (HQ700698) formed a clade with two species of Helicotylenchus and occupied a paraphyletic position. This phylogenetic tree clearly showed the paraphyly of the Hoplolaimidae as previously docu mented by other authors (Subbotin et al, 2007;Vovlas et al, 2008;Atighi et al, 2011;Cantalapiedra-Navarrete et al, 2012, 2013. Figure 6 presents a phylogenetic tree constructed using ITS 1 sequence of the new species and 42 species of Rotylenchus and one belonolaim as outgroup taxon.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…As in recent contributions (Cantalapiedra-Navarrete et al, 2012, 2013, the phylogenetic relationship showed that R. conicaudaus (HQ700698) formed a clade with two species of Helicotylenchus and occupied a paraphyletic position. This phylogenetic tree clearly showed the paraphyly of the Hoplolaimidae as previously docu mented by other authors (Subbotin et al, 2007;Vovlas et al, 2008;Atighi et al, 2011;Cantalapiedra-Navarrete et al, 2012, 2013. Figure 6 presents a phylogenetic tree constructed using ITS 1 sequence of the new species and 42 species of Rotylenchus and one belonolaim as outgroup taxon.…”
Section: Discussionmentioning
confidence: 59%
“…Primers for 28S rRNA gene D2-D3 amplification were forward primer D2a (5'-ACAAGTACCGTGAGGGAAAGT-3') and re verse primer D3b (5'-TGCGAAGGAACCAGCTACTA-3') (Nunn, 1992). The forward primer TW81 (5'-GTTTC CGTAGGTGAACCTGC-30 and reverse primer 5.8SM5 (5'-GGCGCAATGTGCATTCGA-3') were used for am plification of the ITS 1-rRNA gene (Vovlas et al, 2008). PCR was carried out in a total volume of 30 /i\ (16.7 /A distilled water, 3 /A lOx PCR buffer, 0.6 /A 10 mMd NTP mixture, 1.2 /A 50 mM MgCl2 , 1.5 /A of each primer (lOpmol /xl-1), 0.5 /A of Taq DNA polymerase (5U /A~x, CinnaGen) and 5 /A of DNA template).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular features are considered to be particularly useful where morphological characters lead to an ambiguous interpretation or when dealing with cryptic species which are clearly different based on their genes, but are difficult to distinguish based on morphological characteristics (Tandingan De Ley et al 2007;Vovlas et al 2008). Since the identification of X. brevicollum is controversial and morphological analysis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The large num ber of species within the genus (ca 95 nominal species) complicates the identification process and has required the construction of tabular and dichotomous keys, based on a combination of major and supplementary characters, to enable pragmatic morphological identification (Castillo & Vovlas, 2005). Recently, DNA-based approaches have been successfully used for the molecular diagnostics of species of Rotylenchus (Vovlas et al, 2008;Atighi et al, 2011;Cantalapiedra-Navarrete et al, 2013). Phylogenetic studies within Rotylenchus have been carried out based on the D2-D3 expansion region of the 28S and ITS1 rRNA genes, providing initial insights toward resolving phylogenetic relationships among Rotylenchus species, and demonstrating paraphyly of the genus in the majority rule consensus trees within Hoplolaimidae Filipjev, 1934(Subbotin et al, 2007Vovlas et al, 2008;CantalapiedraNavarrete et al, 2012).…”
mentioning
confidence: 98%